2017
DOI: 10.4103/jispcd.jispcd_131_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antiplaque efficacy between essential oils with alcohol-based and chlorhexidine with nonalcohol-based mouthrinses

Abstract: Aim and Objectives:The aim of this study is to compare the antiplaque efficacy of alcohol-based mouthwash with essential oils and nonalcohol-based chlorhexidine mouthrinse in 4 days plaque re-formation study.Materials and Methods:The current research paper is double-blinded, parallel designed clinical trial that was conducted in the Department of Periodontics and Oral Implantology, Kalinga Institute of Dental Sciences, Bhubaneswar. This included ninety dental students of Bachelor of Dental Surgery curriculum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
7
0
1
Order By: Relevance
“…However, in the present study, the individuals in the periodontitis group underwent full-mouth scaling plus CHX, as described by Quirynen et al 25 , instead of EO. Despite some undesirable side effects due to its higher anti-plaque effectiveness, CHX is the first option for the short-term chemical dental biofilm control of periodontitis 14,[26][27][28][29] . Thus, whether a longer period of time is needed to observe the total protein level reduction in the presence of periodontitis is a subject for further studies, especially when considering the improvements in the classical clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, the individuals in the periodontitis group underwent full-mouth scaling plus CHX, as described by Quirynen et al 25 , instead of EO. Despite some undesirable side effects due to its higher anti-plaque effectiveness, CHX is the first option for the short-term chemical dental biofilm control of periodontitis 14,[26][27][28][29] . Thus, whether a longer period of time is needed to observe the total protein level reduction in the presence of periodontitis is a subject for further studies, especially when considering the improvements in the classical clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this group received oral hygiene instructions and rinsed with an EO mouthwash, which, according to Raslan et al 13 , provided additional benefits when compared to isolated mechanical procedures. Studies that have compared EOs with CHX demonstrated that EOs are a viable option for gingivitis patients due to their appropriate clinical benefits with less side effects 14,[26][27][28][29] . The present gingivitis patients showed statistically significant improvements at 3 months, as revealed by the PD, PI, and GI reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The present study comprised 200 dental students 18–22 years of age, with gingival index of Score II (According to Loe and Silness (1963));[ 6 ] were randomly divided into two groups of 100 each ( n = 100). The first group was advised to rinse with 15 ml 0.12% chlorhexidine (CHX) mouthwash, and the second group with 15 ml of formulated herbal mouthwash twice daily for 30 s for 15 days along with their regular tooth brushing with a standard toothbrush and paste with no other restrictions in par with real-life situation.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Naturally available herbs such as tulsi, triphala, neem, honey, ajwain, turmeric, etc., have been commonly used either alone or in combination as safe and effective antibacterial agents. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils have been used in the oral cavity for decades, with excellent results as agents that aid mechanical control (Haas et al, 2016). Most are used in mouthwash solutions (Kulkarni, Singh, Jalaluddin, & Mandal, 2017;Thomas, Thakur, & Mhambrey, 2015). However, coadjuvant chemical control has also been used in other forms such as dentifrices and subgingivally positioned slow-release devices (Ower, Ciantar, Newman, Wilson, & Bulman, 1995;Pessan, Al-Ibrahim, Buzalaf, & Toumba, 2008).…”
Section: ? (To All Analyses)mentioning
confidence: 99%